(untitled) (Global Journal of Human-Social Science, 2025)
This paper analyzes how the digital renminbi e-CNY may impact the structural power of the U S dollar and discusses its primary limitations We adopt the framework of the dollar s structural power within US hegemony highlighting the political consequences of its central role Next we examine China s digitalization from two perspectives monetary and operational and within the context of the Digital Silk Road whose four pillars infrastructure technology e-commerce and governance support the e-CNY s dissemination This paper argues that the e-CNY s launch might provide a new impetus for the renminbi s internationalization particularly in regional payments and e-commerce However this does not challenge the dollar s structural dominance in the short term as the limits to the expansion of the e-CNY in the international monetary hierarchy remain quite significant